Understanding crime prevention : from theory to practical application - Henson, Billy (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"This book offers a concise and authoritative overview of the full scope of crime prevention, including foundations, theory, application, and techniques. It details how theory sets the groundwork for the practical application of successful crime prevention strategies and illustrates the foundations of and need for crime prevention, the best approaches to implementing crime prevention programs, and the issues that need to be considered when evaluating crime prevention programs. The book is split into three sections which include: - Theoretical Foundations. This section includes a brief overview of the history and growth of crime prevention as a field of study, and in practice. - Crime Patterns and Concentration. This section covers the causes and effects of both large and small-scale crime concentration, with particular focus on the development of major forms of crime concentration, including hotspots, risky facilities, hot products, repeat offenders, and recurring victims. - Crime Prevention Application. This section is centered on the practice of crime prevention, focusing on the development and implementation of actual crime prevention programs, including the role of both law enforcement and non-law enforcement agencies. Understanding Crime Prevention has built-in pedagogical features, including a range of tables, boxed examples, and case studies, as well as discussion questions. This book is essential reading for advanced courses on crime prevention, as well as related courses on policing, crime control, theory, and criminal justice"--
(3ebQQGJ OQGSjI (B2025-2026.s
Includes bibliographical references and index.
Keywords: Crime prevention